Castor Bean (Ricinus communis L.) - A Biofuel Plant: Morphological and Physiological Parameters Propagated from Seeds in Bangladesh - Nahar, Kamrun (Asian Business Review, 2013)
Pot experiments were carried out in Dhaka, Bangladesh from March to September 2012 to evaluate the morphological and physiological parameters of Castor oil Plant (Ricinus communis L.), a second generation energy crop propagated from seeds. The leaves and petioles of castor plants were collected from the earthen pot to determine the leaf and petiole nutrient contents. So this study provides a reliable account of the endogenic concentrations of nutrients present in petiole and their content in leaves including the morphological parameters such as plant height, stem diameter, leaf growth, fresh and dry weight of leaves, petiole and root length of the plant at 2 vegetative growth stages grown in Silty clay loam soil were attempted. The experiment revealed that the morphological parameters responded better in mature plant compared to young plant but the physiological parameter showed variations at 2 growth stages.